Problematika Antara Israel dan Palestina - Fitria Fitria; Gilang Rizki Aji Putra (ADALAH, 2022)
This article examines how Indonesian diplomacy takes place in the Israeli-Palestinian conflict. Armed friction and clashes between Palestinian fighters and the Israeli military still occur and can even affect Palestinian civilians. Judging from the history of Indonesia's closeness to Palestine, Indonesia is one of the countries that actively call for the independence of Palestine with a two-state solution. This article is described using conflict resolution theory. Furthermore, the author finds the findings of Indonesian diplomacy in resolving the Israeli-Palestinian conflict, Indonesia plays an active role through its role as a non-permanent member of the UN Security Council.